THE INTEGRATION ARTICULATION BETWEEN THE EDUCATION AND HEALTH ACTIONS IN THE FAMILY HEALTH PROGRAM - PSF - Cesar Cavalcanti da Silva; Ana Tereza M. C. da Silva; Agnes Lonsing (Universidade Federal de Goias, 2006)
ABSTRACT: The article discusses the practical actions of a team of the Family Health Program-PSF in a city of the Northeastern Brazilian region and, it reveals the lack of integration/articulation of those actions with the educational dimension. The disarticulation of the team members' knowledge of health on the theoretical, methodological and philosophical principles of PSF is pointed as one of the determinant of the little involvement of the team work with the educational area. the analysis of the collected data was accomplished through the technique of the critical Analysis of the speeches that led to the empiric category: contradiction theoretical x practice in the actions of the health teams of the Family Health Program. KEY WORDS: Health Education, Family Health Program; Public Health Nursing.